Design of Backend API Payment Gateway System Implementation to Minimize Fraud and Facilitate Payment Transactions at Hattrick Online Game Cafe - Wisnu Sukma Maulana (Asosiasi Dosen Muda Indonesia, 2025)
Hattrick Online Game Cafe has branches in two cities, namely Pemalang and Depok. In addition, this cafe operates almost 24 hours a day, seven days a week, with cashier operations carried out on a morning and evening shift schedule. Furthermore, payments are still made in cash. These conditions have led to several challenges, such as the inability to monitor financial transactions in real time, which could result in fraud or manipulation of cash flow. Another challenge is the need for meticulous attention to detail in calculating payment amounts and cash refunds given by customers to cashiers. Cashier staff may make errors due to fatigue during their shifts, and there is also a need for cash inventory counts as a means of refunding in payment transactions. Finally, the main challenge is the need for transparent and precise financial reports for the café owner as a means of accountability to investors who have and will invest capital in the development of the Hattrick Online Game Café business. Therefore, research on the design and implementation of a backend API Payment Gateway system as a means of customer payment transactions at the Hattrick Online Game Café is expected to address all these issues.